Characteristics of natural and planted sandalwoodsupporting soils in Seoni district, Madhya Pradesh - CHOUDHARI, PUSHPAJEET L.; PRASAD, JAGDISH; SINGH, SAURABH J.; GURAV, PRIYA; GOYAL, KANIKA (Journal of Soil and Water Conservation, 2024)
Two sandalwood-supporting pedons, one planted (P1) and other natural growing, were characterized in Seoni district of Madhya Pradesh. The solum depth of both the pedon was 30 cm underlain by weathered basalt beyond 50 cm. Pedon was dark reddish brown while P2 was characterized by dark reddish brown to dusky red. P2 had sandy clay texture (A1 horizon) and other horizons of both the pedons was associated with clay texture. These soils had more than 35 cmol(p+)kg-1 CEC and dominance of smectite (>20%) followed by vermiculite. There was more than 20 per cent feldspar in Bw horizon of P1 while underlying horizon of P2 had 25 per cent quartz. The nearly neutral soils had more than 1.0 per cent organic carbon barring A2 horizon of P2. These calcareous soils were dominated by exchangeable Ca++ followed by Mg++, Na+, K+ on exchange complex and grouped as Typic Haplustepts and Typic Ustorthents at subgroup level.